Operationalizing tawarruq by Islamic banks in Malaysia: issues, challenges and way forward - Aljamos, Yusof Mahmoud; Abu Jaish, Anas Ahmad; Ibrahim, Khairunisah (International Research Centre of Islamic Economics and Finance (IRCIEF), 2018)
Offering viable and competitive Islamic Finance products by banking institutions could be regarded as a crucial roadmap in pursuing and achieving the Sustainable Development Goals (SDGs). Such initiatives strengthen the role of Islamic finance in uplifting financial prosperity, stability and growth. Tawarruq is one of the Islamic finance liquidity providing schemes which is commonly utilized in virtually every country that practices Islamic finance. This research examines the issues and challenges of Tawarruq faced by Islamic banks in Malaysia and the way forward of Tawarruq application. The legality of Tawrruq has been debated by few researchers, which contributes towards the diverse resolutions and rulings from Islamic nations on the lawfulness of Tawarruq. This study is carried out based on a qualitative approach whereby resources are obtained from various secondary sources including journal articles, books and internet websites. Besides, this paper aims to provide views and verdicts of legal scholars with respect to Tawarruq in the banking system. This study also provides the literary evidences and sound arguments in reaching towards the final juristic judgment.